Left : a love story - Hogan, Mary, 1957- (William Morrow, an imprint of HarperCollinsPublishers, 2018)
It started as a dream vacation in Spain, with Fay and Paul Agarra enjoying all the delights of a European holiday. A respected New York City judge, Paul has always been the man Fay can rely on, no matter what. When he inexplicably disappears from a Barcelona street corner, Fay knows something is terribly wrong. Once reunited, Paul shrugs off the episode as a simple misunderstanding<U+2014>but Fay suspects her almost perfect life has taken a dark and sudden turn. Soon there are more signs that Paul is beginning to change. Bouts of forgetfulness lead to mistakes in the courtroom. Simple tasks cause unexplainable outbursts of anger. Fay<U+2019>s worst suspicions are realized when she learns her husband<U+2014>her rock, her love, her everything<U+2014>is succumbing to the ravages of dementia. As her husband transforms before her very eyes, Fay copes with her fears by retreating into a fantasy life filled with promise instead of pain. In Fay<U+2019>s invented world, she imagines herself living a glamorous life free from heartache, with a handsome neighbor she barely knows rescuing her from a future she can<U+2019>t accept.